Strategi Pemasaran Ayam Boiler Di Perternakan UD. RESTU IBU Dengan Menggunakan Metode SWOT - Rozikin, Khoirur; Misbah, Achmad (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2019)
Broiler breeding business is inseparable from several obstacles encountered. The constraint in question is the high level of risk faced in the business of broilers such as the risk of price fluctuations, both input prices such as day old chick (DOC), feed and medicine as well as fluctuations in the selling price of output in the form of live chickens (livebird) and carcasses . Other risks faced are production risks caused by weather, climate, disease and social risks. The purpose of this study is (1) to describe the factors faced by UD. Restu Ibu in marketing broilers, (2) outlines the strategy adopted by UD. Mother's blessing to overcome the factors in marketing broilers, and (3) determine alternative forms of marketing strategies developed by UD. Mother's blessing in marketing broilers. The data analysis technique used is the SWOT analysis.